Pore Structure Characteristics and Its Effect on Mechanical Performance of Cemented Paste Backfill - Huan, Chao; Zhu, Chao; Liu, Lang; Wang, Mei; Zhao, Yujiao; Zhang, Bo; Zhang, Xiaoyan (Frontiers in Materials, 2021)
The development of cemented paste backfilling (CPB) technology has made an important contribution to the mining economy. As a kind of porous material, the pore structure characteristic of cemented paste backfill (CPB) is strongly correlated to its mechanical properties. In this study, CPB specimens were prepared with tailings/cement ratios (T/C ratio) of 4, 6, 10 and curing durations of 3, 7, 14, and 28 days, respectively. Pore structures characteristics of CPB specimens were investigated using nuclear magnetic resonance (NMR) and scanning electronic microscopy (SEM). The uniaxial compressive strength (UCS) was adopted to illustrate the mechanical property of CPB specimens. The coupling effects of T/C ratio and curing time on the pore characteristics of CPB as well as the effect of pore size on the UCS were analyzed. The results indicated that: 1) the microstructural integrity of CPB was highly related to the development status of the pore structure, which can be represented by micro-parameters like porosity, average pore area, etc. 2) a similar normal distribution curve was observed from the four kinds of pore structure in CPB. As the curing time increased, the peak of the pore size curve shifted left, and the peak value decreased, which means that the pore size in CPB decreased and became much concentrated; 3) the extension of the most probable pore size led to the cross-connection of pores and resulted in the fracture of CPB, which was shown as a crack on the main section.